Macedomeris, a new monotypic doderiinine genus (Diplopoda, Glomerida) from a cave in North Macedonia, Balkan Peninsula - Antić, Dragan Ž.; Makarov, Slobodan E. (Zootaxa, 2021)
Here we describe a new monotypic glomerid genus, Macedomeris gen. nov., with Macedomeris ivoi sp. nov. (a presumed troglobiont) as its type species. The new genus clearly differs from all other genera within the order Glomerida by the combination of several morphological characters: the presence of a characteristic deep lateral pit (“Ohrgrube”) on both sides of the thoracic shield, the absence of striking ornamentation on tergites, the fusion of tergite 11 with the anal shield, and the lack of a large medial hump. In addition, Macedomeris gen. nov. differs from other members of the Glomerida by its general appearance, the presence of 2 or 3 vestigial ommatidia and a very wide syncoxite of a 2-segmented leg-pair 17 in the male. Notes on its ecology, troglomorphic features, and relationships with similar members of the tribe Doderiini are also given.